Information Sharing - Benefits - Mendes Calo,Karla (2012)
Government Information Sharing (GIS) allows information exchange and integration between different government departments, agencies, as well as between public and private institutions. Sharing information enables enhanced efficiency - avoiding duplication of processes updating the same data; better quality of processes and services - removing inconsistent data and reducing error; and improved transparency - facilitating access to information. The implementation of GIS initiatives requires technological, organizational, institutional and environmental changes. Therefore, the definition of compeling business cases is required, while studying the feasibility of such initiatives. In this work, we present findigs of our research work studying benefits of GIS. Based on secondary data collection and surveyed GIS initiatives implemented in several countries, we present a comprehensive study of benefits in GIS. The main contribution of this paper is to provide a detailed list of feasible GIS benefits and a classification of such benefits, providing a rigorous benchmark to justify the implementation of GIS initiatives.